Solid phase extraction-based magnetic carbon nitride/metal organic framework composite with high performance liquid chromatography for the determination of tyrosine kinase inhibitors in urine samples. Issue 39 (21st September 2020) - Liu, Donghao; Peng, Jun; Chen, Li; Zhang, Yan; Han, Xiaoyang; Yang, Ping; He, Hua
Abstract : Tyrosine kinase inhibitors were detected by MCN/BIF-20, and this is the first time that BIFs were used for solid-phase extraction. Abstract : In this study, a novel solid phase extraction method was constructed to detect three tyrosine kinase inhibitors (TKIs) in urine with a high-performance liquid chromatography-diode array detector. The sorbent MCN/BIF-20 was constructed by magnetic g-C3 N4 (MCN) and boron imidazole framework-20 (BIF-20) and was characterized by multiple techniques. The experimental results of the adsorption isotherm and adsorption kinetics indicated that the composites had good adsorption of TKIs (148.33 mg g −1, 283.25 mg g −1, 188.17 mg g −1 ). The reason for the good adsorption property of the complex material was revealed by comparison with each single material. The analytical method was built by a single factor experiment, and was evaluated as a suitable method to detect TKIs in urine by its good accuracy (90.35–98.69%), precision (<3.9%), appropriate detection limits (2.2–3.4 ng mL −1 ), and linear ranges (12.5–500 ng mL −1 ) with convenient determination coefficients (>0.9997). The performance of the MCN/BIF-20 composite did not decrease dramatically in 3 cycles. These analytical results demonstrated that g-C3 N4 and BIFs had a bright prospect in sample pretreatment, and the proposed approach based on MCN/BIF-20 was applicable for analysis of TKIs in urine.